Answer:
x > 10
Step-by-step explanation:
Add 3 to both sides.
4 , 7 , 14 , 19 , 21 , 23 , 23 , 26 , 27 , 30
Step-by-step explanation:
HOPE IT'S HELP ;)
Your answer would be option B. 2y² - y - 6 = 0. This is because if you were to substitute x = y² - 1 into the equation 2x - y = 4, you would get 2(y² - 1) - y = 4, which expands into 2y² - 2 - y = 4, and then simplifies to 2y² - y - 6 = 0.
I hope this helps!
Answer:
idk
Step-by-step explanation:
i+d+k= idk
Here is how I would show the work for this problem
5- (a-4) = 3 (a+2)
5-a+4 = 3*a+3*2
5-a+4 = 3a+6
-a+9 = 3a+6
-a+9+a = 3a+6+a
9 = 4a+6
9-6 = 4a+6-6
3 = 4a
4a = 3
4a/4 = 3/4
a = 3/4
So the solution is the fraction a = 3/4 (in decimal form 0.75)
Let me know if you have any questions or issues with any of the steps shown above. It's a lot to take in so feel free to ask about anything really.